Non Typhoidal Salmonella Pyonephrosis in an Asymptomatic Immunocompetent Patient - Seif Mokadem; Mohamed Ali Nouioui; Salma Kalai; Tarek Taktak; Houssem Mediouni; Ramzi Khiari; Samir Ghozzi (Case Reports in Urology)
A 50-year-old man with no past medical history presented with 5 months history of right flank discomfort. Physical examination was unremarkable. CT-scan showed a large right renal pelvic calculi and upper pole hydronephrosis. He underwent open surgical procedure and we peroperatively discovered upper pole pyonephrosis. Bacteriological samples of pus grew group D Salmonella. We prescribed third generation cephalosporin for 14 days. The patient made a steady recovery. Non typhoidal salmonella (NTS) urinary tract infection (UTI) is extremely rare and usually associated with immunosuppressive chronic disease or genito urinary tract abnormalities. Pyonephrosis due to NTS have been reported twice. We report the first case of asymptomatic NTS pyonephrosis.